Creencias asociadas a la hiperplasia prostática benigna - Hamilton Fern·ndez, Stefano Vinaccia (2010)
The purpose of the research is to conduct a review on the rol of the beliefs associated to benign prostatic hyperplasia. Cognitive, behavioral and attitudinal aspects are evaluated related to irrational beliefs with relation to this illness whose prevalence is in the rise in male colombian population.